2018
DOI: 10.1101/348078
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preservation of circadian rhythms by the protein folding chaperone, BiP

Abstract: ER stress and dysregulation of collagen synthesis are associated with progression of disease in cancer and fibrosis. Collagen synthesis is co-ordinated with the circadian clock, which curiously in cancer cells, is deregulated by ER stress. We hypothesised that interplay exists between circadian rhythm, collagen synthesis and ER stress in normal cells. Here we show that fibroblasts with ER stress do not demonstrate circadian rhythms in gene expression upon clock-synchronizing time cues. Conversely, overexpressi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Likewise, the secretory pathway inhibitors Brefeldin A and Monensin also caused inhibition of NLuc-PC-I secretion ( Figure 5 A). Treatment with Brefeldin A, unlike Monensin, resulted in accumulation of intracellular NLuc-PC-I ( Figure 5 B), which is in line with the fact that Brefeldin A is known to induce a strong ER stress response [ 24 ]. Encouraged by these results, we next sought to determine if collagen-DyProQ could be used to evaluate the function of the known antifibrotic therapeutics Nintedanib [ 25 ] and Pirfenidone [ 26 ].…”
Section: Resultssupporting
confidence: 71%
“…Likewise, the secretory pathway inhibitors Brefeldin A and Monensin also caused inhibition of NLuc-PC-I secretion ( Figure 5 A). Treatment with Brefeldin A, unlike Monensin, resulted in accumulation of intracellular NLuc-PC-I ( Figure 5 B), which is in line with the fact that Brefeldin A is known to induce a strong ER stress response [ 24 ]. Encouraged by these results, we next sought to determine if collagen-DyProQ could be used to evaluate the function of the known antifibrotic therapeutics Nintedanib [ 25 ] and Pirfenidone [ 26 ].…”
Section: Resultssupporting
confidence: 71%
“…High‐load eccentric resistance training can reduce pain and improve ECM structural organization in patients with tendinopathy, although this training does not lead to full symptomatic resolution for many patients (63, 64). Recent studies have demonstrated that tendons synthesize collagen during rest phases at night and assemble collagen into mature fibrils during the active day phases (65, 66). Combining the use of recombinant growth factors with properly timed mechanical loading interventions and appropriate rest periods could lead to the improved treatment of tendon disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The proteins that, respectively, control the entrances and exits of the ER and Golgi are 24 h rhythmic, including SEC61, TANGO1, PDE4D, and VPS33B [6,28]. In addition, Pickard et al show that BiP is under the control of the circadian clocks, which take part in the collagen secretion process and assist collagen folding (Figure 1) [29]. In the Clock Δ19 mice with a defective circadian clock, the numbers of collagen and the structure of fibrils are abnormal.…”
Section: The Spatial Structures and Temporalmentioning
confidence: 99%